Combined correction of atrial septal defect, severe pectus excavatum and hydrocele in a young adult male (Community Based Medical Journal, 2018)
Pectus Excavatum (PE) is normally an isolated congenital disorder, but it can also occur with congenital heart defect (CHD). The surgical strategy has evolved over the last 20 years from staged repair to simultaneous repair of both defects. We present a case of using the Nuss procedure for PE during atrial septal defect (ASD) .  A 29 year old male possess detectable systolic murmur along with exertional dyspnea, fatigue of NYHA Class -II functional status and PE. Correction of these morbidities, a surgery was conducted in the Cardiac Surgery Department in July 2017 in Bangladesh Specialized Hospital, Dhaka. Doing a full midline incision, ASD was repaired after Cardiopulmonary bypass was done. The PE correction was done simultaneously with ASD correction. After completion of chest closure, the left sided non-communicating hydrocele was operated on, and tunical sac was excised and averted. After convalescing uneventfully, the patient was discharged.This case shows that in carefully selected cases with concomitant PE and ASD, a combination of the Nuss procedure and ASD repair and also correction of hydrocele.CBMJ 2018 January: Vol. 07 No. 01 P: 35-39